2020
DOI: 10.1192/j.eurpsy.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Eye gaze and facial displays of emotion during emotional film clips in remitted patients with bipolar disorder

Abstract: Background. Aberrant emotional reactivity is a putative endophenotype for bipolar disorder (BD), but the findings of behavioral studies are often negative due to suboptimal sensitivity of the employed paradigms. This study aimed to investigate whether visual gaze patterns and facial displays of emotion during emotional film clips can reveal subtle behavioral abnormalities in remitted BD patients. Methods. Thirty-eight BD patients in full or partial remission and 40 healthy controls viewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Whether ED is an associated feature or a specifier of ADHDwhich defines a specific subtype of the disorder-or even a core feature of the disorder-additional to hyperactivity/impulsivity and inattention-or, finally, a comorbidity, is still a matter of discussion (9). Recent advances in ED research revealed that it can also be a specific feature of youths with BSD (25), and unaffected relatives of BSD youth can still present subthreshold deficits in emotion regulation and processing (26).…”
Section: Introductionmentioning
confidence: 99%
“…Whether ED is an associated feature or a specifier of ADHDwhich defines a specific subtype of the disorder-or even a core feature of the disorder-additional to hyperactivity/impulsivity and inattention-or, finally, a comorbidity, is still a matter of discussion (9). Recent advances in ED research revealed that it can also be a specific feature of youths with BSD (25), and unaffected relatives of BSD youth can still present subthreshold deficits in emotion regulation and processing (26).…”
Section: Introductionmentioning
confidence: 99%
“…As for the raw data provided by the iMotions platform on emotions, they were calculated to obtain a binary result with a threshold of 10, meaning that all those facial expressions that, with at least 10% probability, were rated as such by a human evaluator are given as valid (see Table 2 ). This criterion is the one used by e.g., Kjærstad et al ( 2020 ) and Stanley and Webster ( 2019 ).…”
Section: Resultsmentioning
confidence: 99%